In Vitro Biological and GC-MS Analysis of Whole Plant Calotropis procera - Qahir Shah; Jahangir Khan Achakzai; Muhammad Anwar Panezai; Basira Akhtar; Abdul Manan Kakar; Ali Akbar; Shahabuddin Kakar; Nisar Ahmed Shahwani; Javed Khan; Nazima Yousaf Khan; Ghulam Mustafa Khan; Nizam Baloch; et al. (Journal of Chemistry)
Calotropis procera is a medicinal, traditional, and therapeutic plant in Pakistan. In this research study, the biological activities, for instance, anticancer, antileishmanial, antibacterial, antifungal, anti-inflammatory, and brine shrimp lethality assay and GC-MS are studied. MTT assay, antileishmanial bioassay, microplate Alamar Blue assay, agar tube dilution method, oxidative burst assay using chemiluminescence technique, B-hatching techniques, and triple quadrupole acquisition method MS parameters were the methods used for anticancer, antileishmanial, antibacterial, antifungal, anti-inflammatory, brine shrimp lethality assay, and gas chromatography-mass spectrometry. Whole plant methanol extract of Calotropis procera (WMECP) inhibited 69.1% of the growth of HeLa cell line with an IC50 value of 3.1 ± 0.4 and whole plant n-hexane fraction of Calotropis procera (WHFCP) and whole plant and aqueous fraction of Calotropis procera (WAFCP) inhibited the growth by 70.2% and 65.2% with IC50 values of 5.0 ± 0.3 and 17.1 ± 1.0. Whole plant methanol extract of Calotropis procera (WMECP) inhibited 70.1% of the growth of the PC3 cell line with an IC50 value of 5.1 ± 0.3 and whole plant n-hexane fraction of Calotropis procera (WHFCP) and whole plant aqueous fraction of Calotropis procera (WAFCP) inhibited 61.6% and 59.7% with IC50 values of 3.7 ± 0.5 and 16.4 ± 1.0. None of the extract and fractions of Calotropis procera showed anticancer activities against the 3T3 cell line. None of the extract and fractions of Calotropis procera showed antileishmanial, antibacterial, antifungal, and anti-inflammatory activities. Whole plant methanol extract of Calotropis procera (WMECP) exhibited lethality at the highest concentration while other fractions did not exhibit lethality. GC-MS studies revealed that the whole plant methanol extract of Calotropis procera (WMECP) consists of 11 compounds, whole plant n-hexane fraction of Calotropis procera (WHFCP) consists of 9 compounds, and whole plant aqueous fraction of Calotropis procera (WAFCP) consists of 7 compounds.